The minimalist program - Chomsky, Noam (The MIT Press, 2015)
In his foundational book published in 1995, the author offered a significant contribution to the generative tradition in linguistics. This twentieth-anniversary edition reissues this classic work with a new preface by the author. The author attempts to situate linguistic theory in the broader cognitive sciences, with the chapters formulating and progressively developing the minimalist approach to linguistic theory.